P2.003 Feasibility and Acceptability of Self-Collected Vaginal Swabs For Diagnosis of Bacterial Vaginosis Among Pregnant Women in a Community Setting in Rural Mysore, India. (13th July 2013) - Madhivanan, P; Ravi, K; Wilcox, M; Niranjankumar, B; Shaheen, R; Srinivas, V; Arun, A; Jaykrishna, P; Krupp, K
Abstract : Background: Bacterial vaginosis (BV) is a common cause of adverse birth outcomes. Its association with other obstetric and gynecologic complications and HIV are increasingly recognised. This study examined the acceptability and feasibility of using self-collected vaginal swabs (SVS) for screening of BV in a community setting among rural pregnant women in Mysore Taluk, India. Methods: A community based cross-sectional study was carried out between June 2007 and December 2010. Mobile medical clinics offered antenatal care and HIV testing in all 144 rural villages in Mysore Taluk. Women were also screened for BV using SVS and asked about their experience with the collecting process. Gram-stain evaluation of vaginal samples using Nugent score (NS) was conducted by two trained laboratory personnel. Results: Among the 1675 women attending the mobile medical clinics from the 144 villages, 1541(92%) were included in the analyses. 1639 agreed to provide vaginal swabs (97.8% response rate). The quality of the swabs was satisfactory in 1545 of the cases. There were 134 non-interpretable slides owing to poor quality. The median age of women was 20 years (range 14 to 40 years). Majority (98.7%) reported themselves as Hindus and 1634 (97.5%) were housewives. The prevalence of BV was 9.9% with a NS of 7–10 and 14.9% of women had intermediate flora on Nugent score of 4–6. While 212 women (12.9%) reported collecting the vaginal swab as being 'very easy', 1402 (85%) found it 'easy' and 22 (1.3%) reported it as 'difficult'. Only 12 women were unable to collect the swab for various reasons. Conclusion: These study results support the use of self-collected vaginal swabs for diagnosing BV. Self-collected swabs to detect BV were well accepted by most of rural pregnant women in this region, and the quality of the swabs seemed to be satisfactory.